Dihydropyrimidinase from Saccharomyces kluyveri can hydrolyse polyamides - Quartinello, Felice; Subagia, Raditya; Zitzenbacher, Sabine; Reich, Johanna; Vielnascher, Robert; Becher, Erik; Hall, Mélanie; Ribitsch, Doris; Guebitz, Georg M. (Frontiers in Bioengineering and Biotechnology, 2023)
In Saccharomyces kluyveri, dihydropyrimidinase (DHPaseSK) is involved in the pyrimidine degradation pathway, which includes the reversible ring cleavage between nitrogen 3 and carbon 4 of 5,6-dihydrouracil. In this study, DPHaseSK was successfully cloned and expressed in E.coli BL-21 Gold(DE3) with and without affinity tags. Thereby, the Strep-tag enabled fastest purification and highest specific activity (9.5 ± 0.5 U/mg). The biochemically characterized DHPaseSK_Strep had similar kinetic parameters (Kcat/Km) on 5,6-dihydrouracil (DHU) and para-nitroacetanilide (pNAA), respectively, with 7229 and 4060 M-1 s-1. The hydrolytic ability of DHPaseSK_Strep to polyamides (PA) was tested on PA consisting of monomers with different chain length (PA-6, PA-6,6, PA-4,6, PA-4,10 and PA-12). According to LC-MS/TOF analysis, DHPaseSK_Strep showed a preference for films containing the shorter chain monomers (e.g. PA-4,6). In contrast, an amidase from Nocardia farcinica (NFpolyA) showed some preference for PA consisting of longer chain monomers. In conclusion, in this work DHPaseSK_Strep was demonstrated to be able to cleave amide bonds in synthetic polymers, which can be an important basis for development of functionalization and recycling processes for polyamide containing materials.